Enhancing biodiversity preservation on privately owned land : an analysis of New Zealand's policy approach : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Economics at Massey University, Palmerston North, New Zealand - Lane, Helen (Massey University, 2002)
A large amount of New Zealand's critical remaining habitat for endemic species is located on private land. This research investigates the factors effecting the achievement of the government's response to the decline of New Zealand's indigenous biodiversity on private land. A central theme is that biodiversity policy proposed at central government level is diluted when actually implemented. Focus will be on landowner incentives to preserve native areas. Landowner incentives are seen as being important because economic agents are guided in their behaviour by the incentives made available to them. A case study approach is used to examine the application of the principal policy tools proposed in the government's response to biodiversity decline, and regional variations in policy implementation are considered. A survey is used to identify what incentives would be required for landowners to preserve their native areas. The analysis suggests that the government's initiatives are not likely to achieve the desired result of 'no net loss' of biodiversity stipulated in biodiversity policy documents. Additional incentive measures are needed, particularly where larger areas of vegetation are concerned. The current voluntary approach favours individual landowners who already have a preference to conserve. Those who do not are excluded by the current policy approach, leaving large areas of native vegetation vulnerable to neglect or destruction. Many landowners will require financial incentives to help them change their current conservation preferences. Financial assistance will also enable larger areas of native vegetation to be actively preserved, as many landowners may not be able to afford preservation activities without assistance.
Keywords: New Zealand; Biodiversity conservation; Government policy